2015
DOI: 10.1634/theoncologist.2014-0424
|View full text |Cite
|
Sign up to set email alerts
|

A Phase IIb Trial Assessing the Addition of Disulfiram to Chemotherapy for the Treatment of Metastatic Non-Small Cell Lung Cancer

Abstract: Background. Disulfiram, an alcohol aversion agent, has been in use for .50 years. Numerous authors have reported an anticancer effect of this drug in vitro and in mouse models. More recently, several reports have claimed that disulfiram also possesses anti-stem cell activity. We set out to obtain initial data regarding the safety of combining this drug with chemotherapy and the possible effectiveness of disulfiram in a combination regimen in non-small cell lung cancer (NSCLC). Methods. This phase II, multicent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
110
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(112 citation statements)
references
References 0 publications
1
110
0
1
Order By: Relevance
“…Another attractive feature of DSF is the tolerability and safety demonstrated over years of clinical experience with a large number of patients, and also in the NSCLC patients [34]. Plasma concentrations of DSF in several reports [37, 38], reaching even above 100 μM, routinely exceeded the IC 50 of the in vitro kinase assay described here, so SNARK inhibitory concentrations are expected to be achieved safely in patients.…”
Section: Discussionmentioning
confidence: 96%
“…Another attractive feature of DSF is the tolerability and safety demonstrated over years of clinical experience with a large number of patients, and also in the NSCLC patients [34]. Plasma concentrations of DSF in several reports [37, 38], reaching even above 100 μM, routinely exceeded the IC 50 of the in vitro kinase assay described here, so SNARK inhibitory concentrations are expected to be achieved safely in patients.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, such MnPs are prospective for clinical development as enhancers of ascorbate/H 2 O 2 driven cancer cell killing. CBX is clinically approved for the treatment of esophageal ulceration [41], and different natural compounds as sulfur donors, such as garlic components [42], disulfiram [43], or even the simpliest thiol, H 2 S, bear therapeutic potential [44]. MnBuOE, which we used herein, has excellent safety profile, and shows excellent radioprotection in preclinical studies [14, 15, 24, 45].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence suggests that DSF possesses potential anti-tumor activities both in vitro and in vivo [17][18][19]. The addition of DSF to a combination regimen of cisplatin and vinorelbine appeared to prolong survival in patients with newly diagnosed NSCLC in clinical trials [20]. In this work, we have demonstrated that Ag ions alone or the combination of Ag ions and DSF induces the accumulation of ubiquitinated proteins mainly through inhibition of proteasomal DUBs.…”
Section: Introductionmentioning
confidence: 65%